Effect of Type 2 Diabetes on Bone Mineral Density: A Prospective Observational Study - Sindhu Sujeeth Hegde; Anupa John; Ashna Chackochan; Leelavathi D. Acharya; Shubhada Karanth; Shivashankara Kaniyoor Nagri (APIK Journal of Internal Medicine, 2025)
Context: Diabetic osteopenia, a debilitating complication of type 2 diabetes mellitus (T2DM), is an underestimated entity in general practice. Aims: This study investigated the effects of T2DM and its complications on bone mineral density (BMD) compared to healthy controls. Materials and Methods: This prospective case–control study was conducted between October 2017 and May 2019, recruiting 172 T2DM patients and 172 healthy controls. All the participants underwent BMD assessment using quantitative ultrasound. Fasting blood glucose and glycated hemoglobin levels were also measured. Statistical analysis was performed using SPSS version 23. Results: A significant reduction was observed in the mean t-score values in the T2DM group as compared to the healthy controls (−0.83 ± 1.21 vs. −0.51 ± 1.25, P = 0.015). Furthermore, a longer duration of T2DM could be a risk factor for lower BMD in male patients (P = 0.012). Age was an independent risk factor for reduced bone health, irrespective of the disease status. However, diabetic complications were not associated with BMD levels. Conclusions: Our study demonstrates that patients with T2DM had significantly lower BMD levels compared to healthy individuals, highlighting a potential increased risk for bone fragility and fractures in this population. Furthermore, a negative correlation was found between diabetes duration and BMD.